“My team made me do it”: the differential influence of team amotivation on leaders’ destructive leadership behavior, from a gender perspective - Mats Reinhold; Britt-Inger Keisu; Robert Lundmark; Andreas Stenling; Susanne Tafvelin (Cogent Psychology)
Destructive leadership does not occur in a vacuum; rather, these behaviors are part of a social process in which leader and follower interact and influence each other. Still, knowledge regarding followers’ behaviors as antecedents to destructive leadership behavior is limited, even more so from a gender perspective. In this study, we investigate the relationship between perceived lack of team motivation and destructive leadership behavior, with the leader’s gender as a moderator. Together with Statistic Sweden, we collected data using a two-wave survey design. We included 784 participants in the analysis, using structural equation modeling (SEM). The results showed that perceived lack of team motivation was associated with active and passive destructive leadership behaviors. Beyond that, the leader’s gender moderated the relationship between leaders’ perception of team amotivation and active destructive leadership. The results show that male leaders are more prone to act destructively when they perceive a lack of team motivation. These results suggest that male leaders may be more susceptible to engaging in destructive leadership behaviors due to identity threat than female leaders. Therefore, we examine how the construction of gender and identity and the close association between masculinity and leader identity contribute to the risk of engaging in destructive leadership behavior.